"Human factor" in emergency situations development at Nuclear Power Plants in the conditions of war - Shevchenko, V. V.; Shevchenko, A. S.; Kucherenko, S. M.; Kucherenko, N. S. (Харківський національний медичний університет, 2022)
Since the beginning of Ukraine's full-scale war with the russian federation, the personnel of two Ukrainian Nuclear Power Plants (NPP) (Chornobyl and Zaporizhzhya) have been held hostage by the russian occupiers and subjected to intimidation and abuse. An additional strong stress factor can significantly affect the decision-making of NPP control panel operators, increases the proba-bility of erroneous actions in the event of emergency situations, and can even become their cause. The purpose of our study was to determine the possible influence of the "human factor" on the development of emergency situations, as well as additional parameters for monitoring the health and psychological state of NPP operators working as hostages. Fourteen expert psychologists with at least 10 years of experience in the field of extreme psychology were involved in the study. After the introductory seminar, they were offered a questionnaire to determine the range of pro-fessionally important qualities that have the greatest impact on the effectiveness of professional activity. The results of the expert evaluation became a hypothesis for the next stage of research on the possible influence of the temperament of operators on resistance to the stress of captivity. The technique of professiograms and psychograms separation, methods of scaling and balancing, methods of mathematical statistics and system analysis were used for the research. One hundred and twenty-four anonymous psychological examination cards and occupational profiles of NPP control panel operators who received a license for professional activity in Ukraine or improved their qualifications within the period of 2017‒2020 were analyzed. The predominant types of psychological reactions according to subjective-objective indicators in response to significant stressful situations were studied, and the types of temperaments were determined. The ability to perform professional functions at high and medium levels was recorded in 79 sanguine operators (63.2% of the total number of examined), in 16 choleric operators (12.8%), and was not recorded in melancholic operators. Also, high and medium levels of neuropsychological stability of oper-ators were recorded in 74 sanguine operators (59.2% of the total number of examined), in 6 chol-eric operators (4.8%), and was not recorded in melancholic operators. To assess the psychological state of NPP control panel operators, it is proposed to use a retrospective analysis of interrelated parameters necessary for the performance of professional functions and indicators of neuropsy-chological stability. The study of additional parameters of the psychological state will allow to reduce the influence of the "human factor" on the risks of creating or untimely correction of emer-gency situations.
"Людський фактор" у розвитку надзвичайних ситуацій на атомних електростанціях в умовах війни
Keywords: professionally important qualities; nuclear terrorism; hostages; performance of professional functions; neuropsychological stability; NPP control panel operators